Optimalisasi program GLS melalui program inovatif LITERGUSI (literasi guru dan siswa) di SMP AL FALAH, Jatirahayu, Pondok Melati, Bekasi - Prameswari, Jatut Yoga; Susanti, Dewi Indah; Hamid, Slamet (Presisi Jurnal Pengabdian Masyarakat, 2023)
Indonesia in terms of literacy can be said to be far behind other countries in the world, in 1997, the Program for International Students Assessment (PISA) stated that Indonesia was ranked 40th out of 41 countries. The Ministry of Education at that time issued the Permendikdud regarding the school literacy movement (GLS). GLS does not only prepare a reading room, but also needs to design and condition the situation so that the goals and benefits of GLS can be realized. Currently, schools have not been able to implement GLS optimally because of the lack of known GLS information. This situation is also experienced by teachers at SMP Al Falah Jatirahayu, Pondok Melati, Bekasi. Teachers feel the need to hold socialization and education regarding Optimizing the GLS Program Through the Innovative Literacy Program (Teacher and Student Literacy) so that they can be consistent and understand well the mandate from the Minister of Education and Culture regarding GLS which will be implemented at Al Falah Middle School. For this reason, this socialization needs to be carried out to increase the progress of the GLS program at SMP Al Falah Jatirahayu, Pondok Melati, Bekasi.